Comparative Performance Analysis of Bamboo-based (Bambusa vulgaris) Activated Carbon produced through Carbonization and Activation Processes - Christopher Akinbile; E. M. Epebinu; O.O. Olanrewaju; A.T. Abolude (Nigerian Journal of Technological Development, 2023)
Activated carbon (AC) is one of the numerous cost-effective inputs for treating wastewater in an efficient and cost-effective manner, and several materials have been used to produce AC with diverse results. One such material with a large potential is African Bamboo (Bambusa vulgaris), especially due to its availability. In this study, bamboo was carbonized and then activated using trioxonitrate (V) acid (HNO3) and potassium hydroxide (KOH) as activating agents. The AC was characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) technologies at 50 μm, 80 μm, 100 μm, and 200 μm magnification. The SEM imagery results at 50 μm and 1500x magnification showed that the AC produced using KOH had the largest and most well-developed pore spaces hence maximum capacity to absorb contaminants compared to HNO3's AC and inactivated carbonated charcoal. The FTIR spectra peak analysis results also confirmed that KOH's AC had the highest number of functional groups on its surface and, therefore, enhanced its adsorption capacity.